Guyton and Hall textbook of medical physiology - Hall, John E. (John Edward) 1946-; Hall, Michael E. (Michael Edward) (Philadelphia, PA Elsevier, 2021)
Known for its clear presentation style, single-author voice, and focus on content most relevant to clinical and pre-clinical students, Guyton and Hall Textbook of Medical Physiology, 14th edition, employs a distinctive format to ensure maximum learning and retention of complex concepts. A larger font size emphasizes core information, while supporting information, including clinical and examples are detailed in smaller font and highlighted in pale lavender - making it easy to quickly skim the essential text or pursue more in-depth study. This two-tone approach, along with other outstanding features, makes this bestselling text a favorite of students worldwide. Offers a clinically oriented written with the clinical and pre-clinical student in mind, bridging basic physiology with pathophysiology. Focuses on core material and how the body maintains homeostatis to remain healthy, emphasizing the important principles that will aid in later clinical decision making. Presents information in short chapters using a concise, readable voice that facilitates learning and retention. Contains more than 1200 full-color drawings and diagrams -all carefully crafted to make physiology easier to understand. Features expanded clinical coverage including obesity, metabolic and cardiovascular disorders, Alzheimer's disease, and other degenerative diseases. Includes online access to interactive figures, new audio of heart sounds, animations, self-assessment questions, and more. Enhanced ebook version included with purchase. Your enhanced ebook allows you to access all of the text, figures, and references from the book on a variety of devices
Unit I Introduction to physiology: the cell and general physiology -- Unit II Membrane physiology, nerve, and muscle -- Unit III The heart -- Unit IV The circulation -- Unit V The body fluids and kidneys -- Unit VI Blood cells, immunity, and blood coagulation -- Unit VII Respiration -- Unit VIII Aviation, space, and deep-sea diving physiology -- Unit IX The nervous system: A. general principles and sensory physiology -- Unit X The nervous system: B. the special senses -- Unit XI The nervous system: C. motor and integrative neurophysiology -- XII Gastrointestinal physiology -- Unit XIII Metabolism and temperature regulation -- Unit XIV Endocrinology and reproduction -- Unit XV Sports physiology
Revised edition of: Guyton and Hall textbook of medical physiology / John E. Hall. 13th edition. [2016]
Includes bibliographical references and index
Also available as electronic reproduction
Keywords: Human physiology; Physiology, Pathological